IS SURVIVIN LEVEL IDENTICAL BETWEEN ADENOMAS OF PROXIMAL AND DISTAL COLON? - Marian Adamkov; Sandra Hurta Csizmar; Veronika Mestanova; Desanka Vybohova; Bibiana Krajnakova (Asociación Argentina de Anatomía Clínica, 2022)
Objectives: Considerable differences are known between proximal and distal colon, these include embryological, anatomical, histological, biochemical, and physiological characteristics. Above mentioned distinctions may influence development of variable clinico-morphological entities. Multifunctional antiapoptotic protein survivin participates in regulation of cell cycle, apoptotic cascades, and stimulates angiogenesis. Material and methods: We assessed immunohistochemically expression pattern of antiapoptotic protein survivin in a panel of 243 colon adenomas to determine its association with colon localization. In each section, subcellular compartmentalization of survivin and intensity of immunoreaction were evaluated. Results: Survivin was expressed in 190 cases (78.2%). Statistical analysis confirmed a significant correlation of subcellular survivin compartmentalization and intensity of immunoreaction with colon localization of adenomas. Conclusions: Taking into account unique features of survivin, its expression pattern in proximally sided adenomas, and distinctions between left and right colon, we suppose that survivin level may contribute to higher proliferative phenotype of proximal adenomas.